Index insurance quality and basis risk: Evidence from northern Kenya - Jensen, Nathaniel D.; Barrett, Christopher B.; Mude, Andrew G. (Wiley, 2016)
The number of index insurance pilots in developing countries has grown tremendously in recent years, but there has been little progress in our understanding of the quality of those products. Basis risk, or remaining uninsured risk, is a widely recognized but rarely measured feature of index insurance product quality. This article uses eight semi‐annual seasons of longitudinal household data to examine the distribution of basis risk associated with an index‐based livestock insurance (IBLI) product in northern Kenya. We find that IBLI coverage reduces exposure to covariate risk due to large shocks and mitigates downside risk substantially for many households, even at commercial premium rates. But index insurance is no magic bullet; insured households continue to face considerable basis risk. Examining the components of basis risk, we find that IBLI reduces exposure to covariate risk due to high loss events by an average of 63%. The benefits of reduced covariate risk exposure are relatively small, however, due to high exposure to seemingly mostly random idiosyncratic risk, even in this population often thought to suffer largely from covariate shocks. The result is that IBLI policyholders are left with an average of 69% of their original risk due to high loss events. This research underscores the need for caution when promoting index insurance as a risk mitigation tool, as well as the importance of product quality evaluation.